Love from The crayons - Daywalt, Drew (Penguin Workshop, 2019)
Ring in Valentine's Day--and love--with the New York Times Best-Selling Crayons! This charming new title featuring everyone's favorite coloring crew is the perfect gift for that special someone on Valentine's Day--or any day of the year. Love is yellow and orange. Because love is sunny and warm. Love is purple. Because it's okay to love outside the lines. This special gift book, featuring all the The Crayons from The Day the Crayons Quit, explores the bright colors and subtle shades of love. This is a must-have for fans of The Crayons, and the perfect gift for that special someone.